Endothelial Cell–Derived von Willebrand Factor Is the Major Determinant That Mediates von Willebrand Factor–Dependent Acute Ischemic Stroke by Promoting Postischemic Thrombo-Inflammation. Issue 9 (September 2016) - Dhanesha, Nirav; Prakash, Prem; Doddapattar, Prakash; Khanna, Ira; Pollpeter, Molly J.; Nayak, Manasa K.; Staber, Janice M.; Chauhan, Anil K.
Abstract : Objective—: von Willebrand factor (VWF), which is synthesized in endothelial cells and megakaryocytes, is known to worsen stroke outcome. In vitro studies suggest that platelet-derived VWF (Plt-VWF) is biochemically different from the endothelial cell–derived VWF (EC-VWF). However, little is known about relative contribution of different pools of VWF in stroke. Approach and Results—: Using bone marrow transplantation, we generated chimeric Plt-VWF mice, Plt-VWF mice that lack ADAMTS13 in platelets and plasma (Plt-VWF/ Adamts 13 −/− ), and EC-VWF mice to determine relative contribution of different pools of VWF in stroke. In brain ischemia/reperfusion injury model, we found that infarct size and postischemic intracerebral thrombo-inflammation (fibrin(ogen) deposition, neutrophil infiltration, interleukin-1β, and tumor necrosis factor-α levels) within lesions were comparable between EC-VWF and wild-type mice. Infarct size and postischemic thrombo-inflammation were comparable between Plt-VWF and Plt-VWF/ Adamts 13 −/− mice, but decreased compared with EC-VWF and wild-type mice ( P <0.05) and increased compared with Vwf −/− mice ( P <0.05). Susceptibility to FeCl3 injury–induced carotid artery thrombosis was comparable between wild-type and EC-VWF mice, whereas Plt-VWF and Plt-VWF/ Adamts 13 −/− mice exhibited defective thrombosis. Although most of the injured vessels did not occlude, slope over time showed that thrombus growth rate was increased in both Plt-VWF and Plt-VWF/ Adamts 13 −/− mice compared with Vwf −/− mice ( P <0.05), but decreased compared with wild-type or EC-VWF mice. Conclusions—: Plt-VWF, either in presence or absence of ADAMTS13, partially contributes to VWF-dependent injury and postischemic thrombo-inflammation after stroke. EC-VWF is the major determinant that mediates VWF-dependent ischemic stroke by promoting postischemic thrombo-inflammation. Abstract : Supplemental Digital Content is available in the text.